Partial duplication of the vas deferens at the level of inguinal canal - (:unkn) unknown (WILEY, 2005)
A case of partial duplication of vas deferens is reported. The reports relevant to this malformation are reviewed and the embryologic etiology is discussed.
Keywords: vas deferens; partial duplication; varicocele